Effects of quercetin on in vitro rumen fermentation parameters, gas production and microflora of beef cattle - Xiao, Ming; Du, Liu; Wei, Manlin; Wang, Yajing; Dong, Chenyang; Ju, Ji; Zhang, Runze; Peng, Wen; Wang, Yuxiang; Zheng, Yongjie; Meng, Weijing (Frontiers in Microbiology, 2025)
Methane is an important component of greenhouse gases, and ruminant production is a significant source of methane emissions. At present, flavonoid feed additives have certain applications in methane inhibition in ruminants. However, the effects of different doses of quercetin on rumen fermentation parameters, rumen bacteria and archaea are still unclear. Therefore, this study investigated the effects of quercetin on in vitro rumen fermentation parameters, methane production, and microflora in beef cattle. A completely randomized design was adopted. Quercetin was added to the fermentation substrates at 0% (group C), 0.5% (group Q1), 1% (group Q2) and 1.5% (group Q3). Anaerobic fermentation was carried out at 39°C for 48 h, gas production (GP) was recorded at different times, gas composition was determined, and methane (CH4) production was calculated. Fermentation parameters and dry matter digestibility (DMD) were determined after 48 h. Moreover, rumen fluid was collected for rumen bacterial and archaeal flora determination. The results were as follows: (1) After 32 h of fermentation, the GP decreased in response to the addition of quercetin. With increasing quercetin concentration, the theoretical maximum gas production decreased quadratically before 20 h (Pquadratic = 0.032). There was a quadratic increase in gas production (Pquadratic = 0.024). With increasing quercetin supplementation, the NH3-N content increased quadratically (Pquadratic = 0.027). MCP increased linearly and quadratically with quercetin (Plinear = 0.002, Pquadratic = 0.005), whereas DMD decreased linearly and quadratically with quercetin (Plinear = 0.013, Pquadratic = 0.032). Both 0.5 and 1% quercetin significantly reduced the butyrate content (Pquadratic = 0.002). With the addition of quercetin, the levels of butyrate, isobutyrate, isovalerate, and total volatile fatty acid (TVFA) first decreased but then increased (Pquadratic < 0.05). (2) With increasing quercetin concentration, methane production (Pquadratic = 0.009) and the methane proportion (Pquadratic < 0.001) decreased quadratically. (3) The ACE index and Chao1 index increased quadratically with quercetin supplementation (Pquadratic < 0.05). The relative abundance of Succiniclasticum in groups Q1 and Q3 increased, whereas the relative abundances of norank_f__norank_o__Rickettsiales and Curtobacterium decreased in all quercetin groups at the genus level (P < 0.05). (4) Quercetin supplementation did not affect the diversity of the archaeal community, but the relative abundance of Methanobrevibacter in group Q2 decreased. Overall, quercetin influenced in vitro rumen fermentation and the bacterial flora to decrease methane production and promote rumen nitrogen utilization and MCP synthesis.